Bragg coherent x-ray diffractive imaging of a single indium phosphide nanowire. (6th May 2016) - Dzhigaev, D; Shabalin, A; Stankevič, T; Lorenz, U; Kurta, R P; Seiboth, F; Wallentin, J; Singer, A; Lazarev, S; Yefanov, O M; Borgström, M; Strikhanov, M N; et al.
Abstract: Three-dimensional (3D) Bragg coherent x-ray diffractive imaging (CXDI) with a nanofocused beam was applied to quantitatively map the internal strain field of a single indium phosphide nanowire. The quantitative values of the strain were obtained by pre-characterization of the beam profile with transmission ptychography on a test sample. Our measurements revealed the 3D strain distribution in a region of 150 nm below the catalyst Au particle. We observed a slight gradient of the strain in the range of ±0.6% along the [111] growth direction of the nanowire. We also determined the spatial resolution in our measurements to be about 10 nm in the direction perpendicular to the facets of the nanowire. The CXDI measurements were compared with the finite element method simulations and show a good agreement with our experimental results. The proposed approach can become an effective tool for in operando studies of the nanowires.